(untitled) (Medical Forum Monthly, 2023)
This case report describes a rare occurrence of coexisting ossifying fibroma (OF) and aneurysmal bone cysts (ABC) in the maxillary sinus (MS) of a 22-year female patient. Patient reported to Dental Clinics of College of Dentistry, Qassim University in December 2022. The initial presentation included proptosis and diplopia in the left eye, which prompted further investigations. Imaging revealed a large complex solid and cystic tumor mass extending into the orbit from the left MS. Endoscopic incisional biopsy confirmed the diagnosis of a cyst of the MS, characterized by a giant cell-rich benign fibro-osseous lesion suggestive of OF, with a secondary ABC. This case highlights the importance of considering these rare entities and their coexistence in the differential diagnosis of MS lesions, emphasizing the role of a biopsy in confirming the diagnosis and guiding appropriate management strategies.